STUDENT PERCEPTION OF MATHEMATICS LEARNING BASED ON THE THEORY OF INTELLIGENCE AND THE ASSOCIATION WITH MATHEMATICAL DISPOSITION OF CLASS XI STUDENTS INTERMEDIATE VOCATIONAL SCHOOL - Aep Sunendar; erik santoso (Universitas Majalengka, 2020)
Learning mathematics in Vocational High Schools (SMK) is often synonymous with memorizing formulas, calculations and is felt to be less important by students than productive subjects. For students who have received a low average grade in mathematics tend to have a decreased enthusiasm for learning and often assess themselves inadequate in mathematics even before trying, this shows an undeveloped mathematical disposition. This negative thinking habit often descends most of the vocational students. Mathematical learning based on multiple intelligence theory can be a fun alternative learning strategy for students, because it accommodates the potential of multiple intelligences that students have to achieve mathematics learning competencies. The purpose of this study is to describe mathematics learning based on compound intelligence theory in class XI Vocational High School, describe students' perceptions of mathematics learning based on compound intelligence theory in class XI Vocational School, describe the mathematical disposition of class XI students using mathematics learning based on compound intelligence theory in SMK students' perceptions of mathematics learning based on multiple intelligence theories with mathematical disposition of class XI students in vocational schools. The research method used is a combined method with quantitative and qualitative approaches. Data collection uses questionnaire instruments, observation sheets, and interviews. Analysis of the data used is descriptive and inferential. The subject of research is the eleventh grade students of SMK in Cikijing sub-district, Majalengka Regency